Penerapan Metode Beyond Centers and Circle Tim dalam Proses Pembelajaran PAUD - Anwar , Kasypul (Jurnal Humaniora dan Ilmu Pendidikan, 2023)
Purpose: Through the BCCT method it is directed to build a variety of children's knowledge by building and creating their own through a variety of experiences in learning activity centers so as to bring out children's creativity. Methodology: This study uses a type of qualitative research with a case study design. Researchers first determine the informants who will be asked for information or information. The data analysis technique used in this study is the Miles and Huberman model analysis technique. The technical steps of the Miles and Huberman model analysis consist of data collection, data reduction, data display (data display), and the process of drawing conclusions (conclusion drawing). Results: Based on the results of the study it can be concluded that the application of the beyond centers and circle team method in the PAUD learning process is carried out by carrying out lesson preparations in the form of daily learning implementation plans (RPPH) which refer to semester programs and weekly programs, arrangement of materials and play tools to be used in centers. Contributions: Learning the BCCT (Beyond Centers and Circle Time) Model in PAUD Banjarmasin City is center learning that is carried out in a moving class and has followed the implementation procedure according to the BCCT model which includes lesson planning teachers have not prepared RPPH as a reference for implementing learning that has a positive or negative impact. negatively, in the implementation the teacher has paid attention to the order of the children's playing steps and in the evaluation, the teacher uses various techniques and forms of learning evaluation.